Hematological manifestations of trichobezoar in a child - S.O. Nykytyuk; R.V. Bodnarchuk; O.R. Boyarchuk; S.S. Levenets; M.V. Dolynna (Zaslavsky O.Yu., 2021)
Background. Trichobezoar is a dense compound in the human stomach, consisting of swallowed hair, food particles, and gastric mucus. Sometimes it passes into the initial part of the small intestine. Its clinical picture is very similar to that of a tumor, so it is necessary to conduct a thorough diagnosis. Materials and methods. The article deals with a case of severe protein-vitamin-iron deficiency anemia in a 5-year-old girl on the background of trichobezoar. Results. The child's condition is severe due to the clinical picture of iron-protein-deficiency anemia of a very severe degree. During her stay in the hospital, the girl's condition deteriorated sharply due to the rapid increase in weakness and pallor of the skin, anasarca. Due to the critical growth of the anemic syndrome, the question of the need for blood transfusion and further surgery arose. Conclusions. The peculiarity of this case is a critical increase in anemia in the absence of classic signs of hemolysis on the background of chronic eating and psychosomatic disorders. Thus, it is necessary to form vigilance in pediatricians to trichobezoar and increase the level of knowledge about the correct diagnostic algorithm in such cases.